Pulmonary Complications of Cancer Therapy - E. I. Zyablova; E. Yu. Krivitskaya; I. G. Voronova (Инновационная медицина Кубани, 2024)
Currently, the literature has limited information on potential risks of pulmonary toxicity in patients receiving anticancer therapy. Nevertheless, this complication is not uncommon in some patients and can manifest in various patterns of changes in the lung parenchyma.